A novel management strategy for removal and degradation of polybrominated diphenyl ethers (PBDEs) in waste printed circuit boards. (December 2019) - Xiu, Fu-Rong; Yu, Xuan; Qi, Yingying; Li, Yifan; Lu, Yongwei; Wang, Yixiao; He, Jiahuan; Zhou, Ke; Song, Zhiqi; Gao, Xiang
Graphical abstract: Highlights: A novel SubCM process is developed for the degradation of PBDEs in waste PCBs. The debromination temperature of PBDEs in SubCM could be reduced by adding NaOH. The removal efficiency of PBDEs from waste PCBs by SubCM + NaOH could reach 100%. Effect of temperature, time, and solid-to-liquid ratio on PBDEs removal was studied. Abstract: Waste printed circuit boards (PCBs) contain a high level of brominated flame retardants (BFRs), among which polybrominated biphenyl ethers (PBDEs) are the most widely used additive BFRs. PBDEs are considered to be a type of persistent organic pollutants (POPs). The efficient removal/degradation of PBDEs in waste PCBs is an urgent problem in electronic waste treatment, but the degradation of PBDEs is a great challenge due to their extreme stability and persistence in nature. In this study, a novel management strategy was developed for removal and degradation of PBDEs in waste PCBs by using a simple subcritical methanol (SubCM) process. The results showed that reaction temperature, residence time, solid-to-liquid ratio, and additive NaOH are key factors influencing the removal of PBDEs from waste PCBs. Under optimal conditions (200 °C, 60 min, 1:20 g/mL), the removal efficiency of ∑ 8 PBDEs from waste PCBs could reach 91.3% and 98.8% for the proposed process of SubCM and SubCM + NaOH, respectively. When the temperature is below 200 °C, highly brominated PBDEs congeners in waste PCBs were degraded into 2, '3, 4′, 6-Tetrabromodiphenyl ether (BDE71) and 2, 4, 4′-Tribromodiphenyl ether (BDE28) after SubCM treatment. 4-Bromophenyl ether (BDE4) and diphenyl ether were generated by the further debromination of BDE71 and BDE28 with the increase of treatment temperature. The debromination temperature of PBDEs congeners in SubCM could be markedly lowered by adding 4 g/L of NaOH. The complete debromination of PBDEs congeners in waste PCBs could be achieved at 300 °C and 250 °C for the developed process of SubCM and SubCM + NaOH, respectively.